Protective effect of Pisonia aculeata on Rifampicin and Isoniazid induced hepatotoxicity in rats - C. Anbarasu; B. Rajkapoor; J. Kalpana (International Journal of Phytomedicine, 2011)
Pisonia aculeata is traditionally used in treatment of liver disorder and thought to have a protective effect which may be beneficial to reduce symptoms of hepatotoxicity. The current study aimed to evaluate the scientific merit of these anecdotal claims in an in vivo model. Methanolic extract of leaves of Pisonia aculeata (250 and 500 mg/kg, p.o.) showed a remarkable hepatoprotective and antioxidant activity against Rifampicin and Isoniazid induced hepatotoxicity as judged from the serum marker enzymes and antioxidant levels in liver tissues. Acetaminophen induced a significant rise in aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALP), total bilirubin, gamma glutamate transpeptidase (GGTP), lipid peroxidase (LPO) with a reduction of total protein, superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), reduced glutathione (GSH), Glutathione reductase (GR), Vitamin C and E. Treatment of rats with different doses of plant extract (200 and 300 mg/kg) significantly (P<0.001) altered serum marker enzymes and antioxidant levels to near normal against acetaminophen treated rats. Also the extract was effectively altered the drug metabolizing enzymes such as Cytochrome P450, NADPH Cytochrome C reductase and glutathione S transferase. The activity of the extract at dose of 500 mg/kg was comparable to the standard drug, silymarin (50 mg/kg, p.o.). Histopathological changes of liver sample were compared with respective control. Results indicate the hepatoprotective and antioxidant properties of Pisonia aculeata against rifampicin and isoniazid -induced hepatotoxicity in rats.